Development and field evaluation of PCR assays based on minimum length Bm86 cDNA fragments required for Rhipicephalus and Hyalomma tick species delineation - Zamiti, Sayed; Mhadhbi, Moez; Dhibi, Mokhtar; Darghouth, Mohamed Aziz; Ben Said, Mourad (Frontiers in Veterinary Science, 2023)
Introduction Hyalomma and Rhipicephalus ticks are important genera that can transmit diseases to both animals and humans, including Crimean-Congo hemorrhagic fever, tick-borne encephalitis, and several types of spotted fever. The accurate identification of tick species is essential for the effective control and prevention of tick-borne diseases. However, traditional identification methods based on morphology can be challenging and subjective, leading to errors. The development of DNA markers has provided more precise and efficient methods for tick species identification, but the currently available markers have limitations in their discriminatory power and sensitivity. To address this need for more sensitive and specific markers, this study aimed to identify two minimum sequence fragments required for tick Hyalomma and Rhipicephalus species identification using the Bm86 cDNA marker, which has previously been shown to be in perfect agreement with the current taxonomy of hard ticks based on its complete sequence. Methods Based on our in silico determination that a minimum sequence of 398 bp for Rhipicephalus spp. (from 1487 to 1884) and 559 bp for Hyalomma species (from 539 to 1097) was necessary for species delineation, two distinct PCR assays were developed to apply these sequences in practice. Results and discussion Discrimination between species within each genus was achieved through sequence homology and phylogenetic analysis following the sequencing of the two PCR products. Subsequently, their performance was evaluated by testing them on the field-collected ticks of the Hyalomma and Rhipicephalus genera obtained from various host animals in different geographic regions of Tunisia. The use of shorter partial sequences specific to the tick genera Rhipicephalus and Hyalomma, which target the tick's RNA banks, could represent a significant advance in the field of tick species identification, providing a sensitive and discriminatory tool for interspecific and intraspecific diversity analysis.